1977
DOI: 10.1128/aac.11.3.528
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-Mediated Beta-Lactamase Production in Neisseria gonorrhoeae

Abstract: Several 8-lactamase-producing, penicillin-resistant strains of Neisseria gonorrhoeae were examined for R plasmids. Penicillin-resistant strains isolated from men returning from the Far East and their contacts contained a 4.4 x 106-dalton plasmid in common. Transformation studies and the isolation of a spontaneous penicillin-susceptible segregant showed that the structural gene for f8-lactamase was part of the 4.4 x 106-dalton plasmid. An additional penicillinresistant gonococcal strain isolated in London was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(64 citation statements)
references
References 27 publications
1
62
0
1
Order By: Relevance
“…Three strains were resistant to ampicillin (minimal inhibitory concentration > 128 ,ug/ml) and produced /8-lactamase as determined by hydrolysis of a chromogenic cephalosporin (23). Since plasmid-mediated 83-lactamase production had been documented in Haemophilus influenzae (10) and Neisseria gonorrhoeae (2,11,26), we wondered if f8-lactamase production might also be plasmid mediated in H. ducreyi and whether there might be any relationship between such a plasmid and the previously characterized plasmids of N. gonorrhoeae and H. influenzae.…”
mentioning
confidence: 99%
“…Three strains were resistant to ampicillin (minimal inhibitory concentration > 128 ,ug/ml) and produced /8-lactamase as determined by hydrolysis of a chromogenic cephalosporin (23). Since plasmid-mediated 83-lactamase production had been documented in Haemophilus influenzae (10) and Neisseria gonorrhoeae (2,11,26), we wondered if f8-lactamase production might also be plasmid mediated in H. ducreyi and whether there might be any relationship between such a plasmid and the previously characterized plasmids of N. gonorrhoeae and H. influenzae.…”
mentioning
confidence: 99%
“…ducreyi from world wide sources are similar and moreover have sequences in common with /Mactamase plasmids in N. gonorrhoeae (Brunton et al 1982). The overall plasmid profiles of many /Mactamase producing N. gonorrhoeae are different; but, since cryptic plasmids are also present, Elwell et al (1977) suggested that insertion of gene sequences into pre-existing plasmids may have occurred. They further speculate that some fragments of DNA could prove exceptionally mobile and, as the extrachromosomal gene pool increases, plasmids with wider abilities to infect diverse groups of organisms will arise and be maintained.…”
Section: The New Hospital Epidemiologymentioning
confidence: 99%
“…Multiple drug resistance emerged a few years later in the 1950s to early 1960s among several gastrointestinal/foodborne pathogens including Escherichia coli, Shigella and Salmonella (FBI) [17]. Multiple drugs resistance has continued to spread among common pathogens, with Haemophilus influenzae developing resistance to ampicillin [18], chloramphenicol and tetracycline [19,20] and an increased resistance to ampicillin observed, with ampicillin-resistant Neisseria gonorrhoea (STI) emerging mainly in developed countries in the 1970s [9,21]. Currently, all WHO regions report very high rates of resistance amongst common bacteria (for e.g.…”
Section: Antimicrobial Resistance and The Water Sanitation And Hygiementioning
confidence: 99%